Microtremor characteristics and analysis of seismicity on Opak fault lines, Bantul district, Yogyakarta - Merizka Marsyelina; Nugroho Budi Wibowo; Denny Darmawan (Jurnal Sains Dasar, 2014)
This research aimed to determine the microtremor characteristics and seismicity analysis around Opak’s fault in  Jetis subdistrict, Imogiri subdistrict,  Pundong  subdistrict, and Kretek subdistrict. This research using HVSR (Horizontal to Vertical Spectral Ratio) method, spectrum analysis, TFA analysis and maximum likelyhood method. The primary microtremor’sdata was taken from 9 points and thesecondary data from 32 point using grid 3 km spacing. The data record the natural waves or seismic signals at each measurement points. The processed data thus characterize the structrure of the soil and rock layers. For seismicity of analysis earthquake data since 2006-2014 from BMKG were used. The results indicate microtremor characteristics around the fault Opak according to the parameter map predominant frequency modeling result, map predominant period modeling result, map amplification factor modeling result, map Vs30 modeling result, curve H/V, curve spectrum and curve TFA which is divided into three zones. Seismicity analysis showed that earthquake around Opakfault earthquake has magnitude between  0,4 to 3,2,  has a depthof 10 km to 20 km, and has a  b-value of 0,44 to 0,76.   Key words: HVSR method, TFA analysis, spectrum analysis, maximum likelihood method, microtremor characteristics, b-value, Opak fault